2014
DOI: 10.1002/jcp.24723
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Osteoclast Multinucleation by the Actin Cytoskeleton Signaling Network

Abstract: Although it is known that osteoclasts are multinucleated cells that are responsible for bone resorption, the mechanism by which their size is regulated is unclear. We previously reported that an actin-rich superstructure, termed the zipper-like structure, specifically appears during the fusion of large osteoclast-like cells (OCLs). Actin cytoskeleton reorganization in osteoclasts is regulated by a signaling network that includes the macrophage colony-stimulating factor (M-CSF) receptor, a proto-oncogene, Src, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 60 publications
5
31
0
Order By: Relevance
“…Downstream of CSF-1R, c-Src activates Rac and inhibits Rho, two small GTPases that regulate the cytoskeleton. While Rac activity is dispensable for osteoclast development and multinucleation (Croke et al, 2011), Src-mediated inhibition of Rho activity is necessary for efficient fusion (Takito et al, 2015). Activated RANK upregulates the expression of the Rho family GTP-ase Wrch (a.k.a.…”
Section: Regulation Of Osteoclasts and Bone Development By Csf-1mentioning
confidence: 99%
“…Downstream of CSF-1R, c-Src activates Rac and inhibits Rho, two small GTPases that regulate the cytoskeleton. While Rac activity is dispensable for osteoclast development and multinucleation (Croke et al, 2011), Src-mediated inhibition of Rho activity is necessary for efficient fusion (Takito et al, 2015). Activated RANK upregulates the expression of the Rho family GTP-ase Wrch (a.k.a.…”
Section: Regulation Of Osteoclasts and Bone Development By Csf-1mentioning
confidence: 99%
“…An active rearrangement of the cytoskeleton is taking place during each cell‐to‐cell fusion, which involves the actin‐dependent cytoskeleton signaling network (Takito et al, ). In order to form multi‐nucleated osteoclasts, single nucleated osteoclast precursors need to go through many rounds of cell–cell fusion.…”
Section: Possible Involvement Of Dc‐stamp In Biological Pathwaysmentioning
confidence: 99%
“…The molecular mechanisms underlying the control of osteoclast cell size remain largely unknown. By using various inhibitors that specifically block the actin cytoskeleton signaling network (Takito et al, ), it has been shown that the size of osteoclasts is regulated by the actin‐mediated cytoskeleton signaling network. Osteoclast polarization is accompanied by extensive reorganization of the actin cytoskeleton.…”
Section: Possible Involvement Of Dc‐stamp In Biological Pathwaysmentioning
confidence: 99%
“…A previous study showed that osteoclast undergoes internal structure changes such as rearrangements of actin cytoskeleton that prepare it to resorb bone [38]. Another study suggested that the status of actin cytoskeleton signaling network determines the size of osteoclast-like cells during cell fusion [41]. As one of the top 10 pathways in our study, 8 genes out of the target gene list were enriched in the pathway “Regulation of actin cytoskeleton”.…”
Section: Discussionmentioning
confidence: 72%